1999
DOI: 10.1007/s00276-999-0119-5
|View full text |Cite
|
Sign up to set email alerts
|

Frequency of septum pellucidum anomalies in non-psychotic population: a magnetic resonance imaging study

Abstract: This prospective MRI investigation was performed to investigate septum pellucidum (SP) anomalies in 505 (242 male, 263 female) non-psychotic persons. The mean age of the population was 39.179 +/- 0.904 (40.461 +/- 1.395 male, 38 +/- 1.166 female). There was no significant difference between the means of age in the male and female groups (t-test, DF = 479, p > 0.05). The SP anomalies were classified as cavitation anomalies (Type I) and absence of the SP (Type II). Type I anomalies were subdivided into four grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 24 publications
1
8
0
Order By: Relevance
“…Kwon et al (1998) argue that the prevalence of CSP is 85% among normal individuals, the highest prevalence observed in the available literature. As opposed to these figures, Aldur et al (1999) reported CSP appearance of not exceeding 1.56% in life-long MRI studies of a non-psychotic population. Congruently, Pauling et al (1998) claimed that most of the non-invasive imaging methods (CT and MRI) provided studies comprised of seriously biased populations.…”
Section: Discussionmentioning
confidence: 58%
“…Kwon et al (1998) argue that the prevalence of CSP is 85% among normal individuals, the highest prevalence observed in the available literature. As opposed to these figures, Aldur et al (1999) reported CSP appearance of not exceeding 1.56% in life-long MRI studies of a non-psychotic population. Congruently, Pauling et al (1998) claimed that most of the non-invasive imaging methods (CT and MRI) provided studies comprised of seriously biased populations.…”
Section: Discussionmentioning
confidence: 58%
“…Kwon and his associates (1998; 19) argued about the prevalence of 85% among normal individuals, which was the highest prevalence in the available literature. As opposed to these figures, Aldur et al (1999; 28) reported CSP appearance not exceeding 1.56% in life‐long MRI studies of a nonpsychotic population. Congruently, Pauling et al (1998; 29) claimed that most of the noninvasive imaging methods (CT and MRI) provided studies composed of seriously biased populations.…”
Section: Discussionmentioning
confidence: 90%
“…The velum interpositum (VI) is a triangular fold of the pia mater (tela choroidea) occupying the transverse cerebral fissure (choroidal fissure) between the diencephalon and the corpum callosum 34 . The VI is located caudal to the interventricular foramen and is interposed between the roof of the thalamus and third ventricle below and the corpus callosum and fornix above.…”
Section: Cavum Veli Interpositi: General Conceptsmentioning
confidence: 99%